Rabies virus neutralization assays: comparison of three fluorescent inhibition tests in cell cultures (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
The Rapid Fluorescent Focus Inhibition Test (RFFIT) and the Fluorescent Antibody Virus Neutralization Test (FAVN) are the rabies virus neutralization assays recognized by World Health Organization and the World Organization for Animal Health, to quantify rabies virus neutralizing antibodies (VNA). In the Pasteur Institute of Sao Paulo/Brazil, the Simplified Fluorescence Inhibition Microtest (SFIMT) is the method used for titration of VNA in serum samples of vaccinated individuals. The aim of this study is the comparison of VNA titration methods: FAVN, RFFIT and SFIMT. One hundred ninety‐three sera samples from dogs and cats were analyzed by the three methods. The statistical tests used to compare the techniques were the McNemar test and Kappa coefficient (CI=95%) to qualitative analyses (